The Suprathermal Particles and Charge Fluctuation Effects on Waves in Complex Plasma - Somayeh Mousavi (JOURNAL OF ADVANCES IN PHYSICS, 2020)
In the frame of kinetic theory, we investigated the effects of suprathermal particles and dust charge fluctuations due to the inelastic collision between the dust grains and plasma particles by calculating the longitudinal dielectric permittivity in an unmagnetized dusty plasma on the wave modes propagating in a complex plasma. The ion and electron distribution were assumed to be Maxwell and kappa distribution in the systems. It was shown that the wave frequency can be analyzed for various values of the spectral index K and the dust charge fluctuations. The Landau damping rate and Propagation rate in dust charge fluctuation presence increase.